Accident causes and organizational culture among avalanche professionals. (April 2016) - Johnson, Jerry; Haegeli, Pascal; Hendrikx, Jordy; Savage, Scott
Abstract: We report on a study of 392 avalanche professionals (AVPRO). We describe their demographics, organizational work environment, and the causes and incidence of accidents. We find evidence of strong and weak cultures of safety among AVPRO organizations and analyze differences between the two with respect to avalanche safety work procedures, personal work skills and attitudes, and causes of accidents. Demographics between the two groups are not different but the perceived causes for accidents were. Those organizations we classify as having a strong culture of safety are identified by their employees as having better avalanche training and reporting procedures and, more positive working behaviors. With respect to accident causes, we report that "operational pressures" and "management overriding personal judgement" during operations were reported by those in organizations with a weak culture of safety as contributing factors. Whereas we find value in large scale surveys of the AVPRO industry, we acknowledge that alternative methods of understanding of organizational culture AVPROs exist and should be utilized. Management implications: ● AVPRO organizations differ with respect to the culture of safety inherent in the organization. While we find no organization with no culture of safety, we can identify them as strong vs. weak. ● AVPRO managers should be cognizant that organizational culture may influence how AVPROs do their job and that causes of accidents may be correlated to a restrictive management culture. ● Communication and better personal decision making are encouraged where an organizational culture of safety exists. ● High risk workers have a high level of self-efficacy independent of management, indicating that their professional and personal skills can be enhanced where management recognizes and rewards independent behavior. ● Because of the dynamic conditions in which the AVPRO mountain community operates, accident causes are rarely simple and linear. They are more likely to be a combination of personal and organizational factors. As such, managers and members of the AVPRO community would benefit from greater understanding of the role of organizational culture in the workplace and could benefit from research in other risk oriented professions.